Injection parameters and lambda effects on diesel jet engine characteristics for JP-8, FAME and naphtha fuels. (1st July 2020) - Yontar, Ahmet Alper
Abstract: The study focused on the effects of lambda, injection duration and start of injection on the diesel jet engine characteristics and also a challenge study for alternative fuels that have similar properties. The high-speed behaviors of the diesel jet test engine at full load were examined experimentally for diesel, JP-8, FAME, and naphtha. The tests were carried out for variations of 1.0–4.0 lambda, 5°–30° injection duration and 4°–20° start of injection. The experimental results were shown comparatively that the trends of sensitivity and behavior for diesel, JP-8, FAME, and naphtha according to variations of the measurement parameters. The behavior of in-cylinder pressure curves showed that FAME was less affected by lambda change than the other fuels. The most affected fuel from the timing of injection was the naphtha for heat release rate. The injection duration variations more positively affected the brake thermal efficiency for FAME than other tested fuels. The FAME was yielded the highest brake specific fuel consumption for the lambda range. At ultra-lean condition, the ignition delay time of naphtha was about 32.27% higher than the other fuels. While the start of injection point increased from 4° to 20°, CO emissions were reduced by about 60% for naphtha usage. The FAME usage had the highest slope and had more sensitivity than other fuels for injection duration variations. The most affected fuel from the start of injection parameter was the diesel for NOx formation. The most extreme sensitivity to injection duration was naphtha for particulate matter formation.